Digital communication competence and teaching performance: quantitative analysis in a Faculty of Translation, Interpreting and Communication Sciences - Aguayo-Meléndez, Aldo (2025)
Digital communicative competence is in constant evolution, requiring reflectionand ongoing updating by university professors. The objective of this research is to determine the level of relationship between digital communicative competence and teaching performance in the Faculty of Translation,Interpreting, and Communication Sciences at a private university in the context of the pandemic. A quantitative correlational approach was applied, with a non-experimental cross-sectional design, using the Digital Communicative Competence Scale by Mateus et al. (2019), along with an ad hoc TeachingPerformance Scale. A positive correlation was found between digital communicativecompetence and teaching performance with in a university setting, thus highlighting the relevance of communicative and digital competencies for improving teaching performance.